Essential guide to food additives - Saltmarsh, Michael (Leatherhead Food International ; Royal Society of Chemistry, 2013)
Food additives have played and still play an essential role in the food industry. Additives span a great range from simple materials like sodium bicarbonate, essential in the kitchen for making cakes, to mono- and diglycerides of fatty acids, an essential emulsifier in low fat spreads and in bread. It has been popular to criticise food additives, and in so doing, to lump them all together, but this approach ignores their diversity of history, source and use. This book includes food additives and why they are used, safety of food additives in Europe, additive legislation within the EU and outside Europe and the complete listing of all additives permitted in the EU. The law covering food additives in the EU which was first harmonised in 1989 has been amended frequently since then, but has now been consolidated with the publication of Regulations 1331/2008 and 1129/2011. This 4th edition of the Guide brings it up to date with the changes introduced by this legislation and by the ongoing review of additives by EFSA. Providing an invaluable resource for food and drink manufacturers, this book is the only work covering in detail every additive, its sources and uses. Those working in and around the food industry, students of food science and indeed anyone with an interest in what is added to their food will find this a practical book full of fascinating details.